Pengaruh Metode Crossword Puzzle terhadap Motivasi Belajar Siswa pada Mata Pelajaran IPS Kelas IX di MTs Sunan Kalijogo Rejosari Kalidawir Tulungagung - Sakina Duwita Febrianti; Bagus Setiawan (Journal Innovation In Education, 2024)
The research was conducted at MTs Sunan Kalijogo Rejosari Kalidawir Tulungagung to overcome obstacles in social studies learning, such as inadequate learning media, monotonous learning methods, and low student learning motivation. This obstacle causes students to be easily bored and less motivated in the learning process. Learning motivation is defined as an impetus that encourages changes in student behavior and provides enthusiasm in learning.This study aims to evaluate the effect of the crossword puzzle method on the learning motivation of ninth grade students at MTs Sunan Kalijogo Rejosari Kalidawir Tulungagung. The crossword puzzle method was chosen because of its ability to attract students' attention through challenging and fun word games. The research used a quantitative true-experimental approach with simple random sampling as the sampling technique. Data were collected through documentation and questionnaires, then analyzed using t-test to measure the significance of the results. The results showed that the use of the crossword puzzle method significantly increased students' learning motivation, with a significance value of 0.000 <0.05. The magnitude of the effect of the crossword puzzle method on students' learning motivation reached 91.9%, indicating that the method is effective in increasing students' learning enthusiasm in social studies subjects.This finding has the potential to contribute to improving the effectiveness of learning in schools, especially in overcoming the problem of low student motivation through the application of innovative and interesting learning methods such as crossword puzzles.